Combined treatment of umbilical cord Wharton’s jelly-derived mesenchymal stem cells and platelet-rich plasma for a surgical patient with hospital-acquired pressure ulcer: a case report and literature review - Zhou, Changhui; Jiao, Linlin; Qiao, Xiaoping; Zhang, Weiwei; Chen, Shuangfeng; Yang, Chunling; Meng, Min (Frontiers in Bioengineering and Biotechnology, 2024)
Hospital-acquired pressure ulcers (HAPUs) are still an important worldwide issue related to the safety and quality of patient care, which are among the top five adverse events reported. Patients who develop HAPUs have longer stays in the hospital than necessary, are at a greater risk of infections, and are more likely to die. Surgical patients are prone to developing PUs because they often remain immobile for extended periods of time, and their surgical procedures may limit the flow of blood oxygen and nutrition and lead to a decrease in muscle tone. Mesenchymal stem cells (MSCs) represent an attractive stem cell source for tissue regeneration in clinical applications, which have been demonstrated to improve wound healing through re-epithelialization, increased angiogenesis, and granulation tissue formation. Here, we present the case of an emergency surgical patient who developed an ulcer on the right heel during hospitalization. The human umbilical cord Wharton’s jelly-derived MSCs (WJ-MSCs) re-suspended in platelet-rich plasma (PRP) were injected into ulcer margins. Four days after the WJ-MSC application, the patient showed progressive healing of the PU. From days 4 to 33, granulation tissue formation and re-epithelialization were clearly observed. The ulcer was almost healed completely on day 47, and the pain in the patient’s wound area also decreased. Thus, intradermal transplantation of WJ-MSCs and PRP was safe and effective for treatment in patients with pressure ulcers. WJ-MSCs, together with PRP, may offer a promising treatment option for wound healing.